[DC] Designing Immersive Tools for Supporting Cognition in Remote Scientific Collaboration - Olaosebikan, Monsurat (2022 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2022)
Scientists collaborate remotely across institutions, countries and continents. However, collaborating remotely is challenging. Video-conferencing tools used for meetings limit the cognitive practices that collaborators can partake in. In virtual reality (VR) users can gain back spatial affordances present in collocated collaboration and we can design interactions that would not be possible in the real world. My research aims to investigate how VR can support cognition in remote scientific collaboration through the design, de-velopment, and study of Embodied Notes: a cognitive support tool designed to be used in a collaborative virtual environment.